Media/lity - between image ban and eucharist - Oorschot, Frederike van; Höhne, Florian (Cursor_, 2023)
In this paper, we want to reflect digital media’s function to bridge absent entities theologically, inspired by two discourses: the thinking about the biblical image-ban after the iconic turn on the one hand and the debates about the Lord's Supper on the other. Of course, this will not lead to a full theory or concept of media and mediality. But it leads to the following main suggestions: We will argue, that the common dualities of "reality" vs. "virtuality" and "embodied" vs. "disembodied" are not appropriate for reflecting digital mediality. Rather, the difference between different media and different media-practices is decisive. This difference is also more decisive than the difference between seemingly unmediated presence and mediated presence. The focus on media all too often hides that seemingly unmediated practices are media practices as well. We will show how different practices - particularly the practice of Eucharist - are already media practices that partake in the dialectic between presence and absence, between making present and withdrawal.